Ultrahigh Strain‐Insensitive Integrated Hybrid Electronics Using Highly Stretchable Bilayer Liquid Metal Based Conductor. Issue 5 (15th December 2022) - Chen, Shuwen; Fan, Shicheng; Qi, Jiaming; Xiong, Ze; Qiao, Zheng; Wu, Zixiong; Yeo, Joo Chuan; Lim, Chwee Teck
Abstract: Human‐interfaced electronic systems require strain‐resilient circuits. However, present integrated stretchable electronics easily suffer from electrical deterioration and face challenges in forming robust multilayered soft‐rigid hybrid configurations. Here, a bilayer liquid‐solid conductor (b‐LSC) with amphiphilic properties is introduced to reliably interface with both rigid electronics and elastomeric substrates. The top liquid metal can self‐solder its interface with rigid electronics at a resistance 30% lower than the traditional tin‐soldered rigid interface. The bottom polar composite comprising liquid metal particles and polymers can not only reliably interface with elastomers but also help the b‐LSC heal after breakage. The b‐LSC can be scalably fabricated by printing and subsequent peeling strategies, showing ultra‐high strain‐insensitive conductivity (maximum 22 532 S cm −1 ), extreme stretchability (2260%), and negligible resistance change under ultra‐high strain (0.34 times increase under 1000% strain). It can act as stretchable vertical interconnect access for connecting multilayered layouts and can be scalably and universally fabricated on various substrates with a resolution of ≈200 µm. It is demonstrated that it can construct stretchable sensor arrays, multi‐layered stretchable displays, highly integrated haptic user‐interactive optoelectric E‐skins, visualized heaters, robot touch sensing systems, and wireless powering for wearable electronics. Abstract : Ultra‐high strain‐insensitive hybrid integrated electronics constructed by a self‐formed amphiphilic bilayer highly stretchable conductor is reported based on liquid metal composite and peeling strategy. The amphiphilic bilayer conductor can self‐solder its interface with rigid electronics, anchor well with substrates, and shows ultrahigh conductivity, stretchability, self‐healability, and interconnect functions. The unique materials hold the potential for strain‐resilient integrated bioelectronics and wearables.